The Unknown Christ of Christianity. Scripture and Theology in Panikkar’s Early Writings, written by Enrico Beltramini - Robinson, Bob (Exchange, 2022)
"The Unknown Christ of Christianity. Scripture and Theology in Panikkar’s Early Writings, written by Enrico Beltramini" published on 22 Dec 2022 by Brill.